Concomitant Infection of Enterotoxigenic Escherichia coli in an Outbreak of Cholera Caused by Vibrio cholerae O1 and O139 in Ahmedabad, India - Chakraborty, Subhra (American Society for Microbiology, 2001)
In Ahmedabad, a major city in the state of Gujarat, India, an outbreak of acute secretory diarrhea caused by Vibrio cholerae O1 Ogawa El Tor, V. cholerae O139, and multiple serotypes of enterotoxigenic Escherichia coli (ETEC) occurred in January 2000. All of the representative V. cholerae O1 and O139 isolates examined harbored the ctxA gene (encoding the A subunit of cholera toxin) and the El Tor variant of the tcpA gene (encoding toxin-coregulated pilus). ETEC isolates of different serotypes were positive for the elt gene, encoding heat-labile enterotoxin. To further understand the molecular characteristics of the pathogens, representative isolates were examined by ribotyping and pulsed-field gel electrophoresis (PFGE). Ribotyping showed that the isolates of V. cholerae O1 Ogawa exhibited a pattern identical to that of the prevailing clone of O1 in areas where cholera is endemic in India, and all of the O139 isolates were identical to the BII clone of V. cholerae O139. PFGE of the representative O1 Ogawa isolates exhibited an identical pattern, comparable to the H pattern of the new clone of O1 reported in Calcutta, India. PFGE analysis of the V. cholerae O139 isolates showed identical patterns, but these differed from the PFGE patterns of O139 isolates reported during 1992 to 1997 in Calcutta. ETEC isolates showed genetic heterogeneity among isolates belonging to the same serotype, although the identical PFGE pattern was also observed among ETEC isolates of different serotypes. Antibiograms of the isolates were unusual, because all of the O139 isolates were resistant to nalidixic acid. Likewise, all of the E. coli isolates showed resistance to ciprofloxacin, norfloxacin, and nalidixic acid. This is a unique outbreak, and we believe that it is the first in which V. cholerae and ETEC were concomitantly involved.